2004
DOI: 10.1093/bja/aeh023
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings of cuffed paediatric tracheal tubes † †Declaration of interest. The investigated paediatric cuffed tracheal tubes were ordered from local distributors and partially provided without charges. No financial support was obtained for the presented work. Dr Weiss and Dr Gerber are actually involved in designing a new cuffed paediatric tracheal tube in co-operation with Microcuff GmbH, Weinheim, Germany.

Abstract: Most cuffed paediatric tracheal tubes are poorly designed, in particular the smaller sizes. A better design of cuffed tubes with a short high-volume, low-pressure cuff, cuff-free subglottic space and adequately placed depth markings are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(20 citation statements)
references
References 33 publications
(7 reference statements)
1
18
0
1
Order By: Relevance
“…The larger tubes are associated with higher incidence of postoperative sore throat, may damage the tracheal mucosa, can cause airway edema, postextubation stridor, subglottic stenosis due to inflated cuff. [12] Moreover, there is great variation in size and shapes of trachea and the correlation between age, height, weight, body surface area and tracheal shape or size is poor. At present, the endotracheal tube is selected according to age and height based formulas, which generally predicted either smaller or larger sizes than proved clinically optimal and there is disparity between age- and height-based formulas and clinically used optimal ETT size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger tubes are associated with higher incidence of postoperative sore throat, may damage the tracheal mucosa, can cause airway edema, postextubation stridor, subglottic stenosis due to inflated cuff. [12] Moreover, there is great variation in size and shapes of trachea and the correlation between age, height, weight, body surface area and tracheal shape or size is poor. At present, the endotracheal tube is selected according to age and height based formulas, which generally predicted either smaller or larger sizes than proved clinically optimal and there is disparity between age- and height-based formulas and clinically used optimal ETT size.…”
Section: Discussionmentioning
confidence: 99%
“…The oversized endotracheal tube relative to trachea or over-inflated cuff between tube and anatomic structures, may damage the tracheal mucosa by friction and compressions, can cause airway edema, postextubation stridor, subglottic stenosis, or cartilaginous ischemia, especially in children. [1] On the other hand, the smaller endotracheal tube will increase the resistance to gas flow and risk of aspiration, insufficient ventilation, and poor monitoring of end tidal gases. [2] The level of the cricoid cartilage plays an important role for selection of the appropriate size endotracheal tube being the narrowest diameter of upper airway.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Cuffed endotracheal tubes (CETTs) in children undergoing surgery have not been very popular because of the fear that the cuff will cause airway mucosal injury, leading to sub-glottic stenosis. [35] Cuffed tubes are more expensive, and their benefit remains unproven. [6] Based on recent studies using magnetic resonance imaging (MRI) scans, it has been postulated that CETTs with low pressure, high volume cuff will seal the airway at the upper trachea where the posterior membranous wall can stretch and produce a complete seal with low cuff pressure of <15 cm H 2 O without any increase in airway complications.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the design of pediatric CETTs from different manufacturers. [5] The authors found that the outer diameters (OD) of the CETTs varied markedly for a given internal diameter (ID), both between tubes of different manufacturers and between UETT and CETT of the same manufacturer. This variation in tracheal tube wall thickness is related to the material used for constructing the tube (PVC, polyurethane, or red rubber).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the study by Bae et al (6), USG frequently underestimated ETT size in patients where the ultrasonographic method was unsuccessful (31 out of 40 patients). In fact, this underestimation can be advantageous for cuffed ETTs when one considers that the bulk of the deflated cuff is not included in the OD (13)(14)(15). However, underestimation may have disadvantages of high airway resistance and increased airway pressures, whereas overestimation is also dangerous as it may cause the selection of a larger ETT, resulting in airway trauma and laryngotracheal damage.…”
Section: Discussionmentioning
confidence: 99%